Laser-induced graphene electrochemical immunosensors for rapid and sensitive serological detection: A case study on dengue detection platform - Supawee Inlumphan; Winadda Wongwiriyapan; Narathon Khemasiri; Prapakorn Rattanawarinchai; Piyawan Leepheng; Panuwat Luengrojanakul; Tuksadon Wuttikhun; Michiko Obata; Masatsugu Fujishige; Kenji Takeuchi; Mayuree Phonyiem Reilly; Teerayut Uwanno; et al. (Sensors and Actuators Reports, 2024)
• LIG electrode was made via CO 2 laser and used as a dengue serology LIG immunosensor. • LIG electrode excellently showed high reproducibility and long shelf-life. • LOD and LOQ of LIG immunosensor was lower than traditional ELISA for 4G2 antibody. • LIG immunosensor showed promising results with dengue serum vs. commercial strip test. Here, we present a diagnostic on a chip platform based on laser-induced graphene (LIG) electrochemical immunosensors for serological detection. The electrochemical immunosensors are fabricated through CO 2 laser induction on polyimide (PI) sheets. Optimal electrochemical activity of LIG electrodes is obtained under optimized conditions of laser fluence. To verify the application, the serological detection platform was demonstrated. After functionalization with dengue virus (DENV) antigen, the LIG electrochemical immunosensors are able to sense the presence of mouse anti-flavivirus monoclonal (4G2) antibody in a wide linear working range of 25–20,000 ng/ml with the limit of detection (LOD) of 17.41 ng/ml. A specific recognition with 4G2 antibodies against with media protein and isotype is confirmed. Furthermore, the reliability of LIG electrochemical immunosensors compared to conventional enzyme-linked immunosorbent assay (ELISA) is verified through the NS1 antibodies identification in human blood serum clinical samples at room temperature. Our results highlight that the LIG-based electrode is a promising platform for electrochemical immunosensors, aimed at developing reliable and practical diagnostic tools for serological detection. These tools enable early diagnosis of infectious diseases, as well as non-invasive and rapid screening.
Keywords: Advanced biosensing and bioanalysis techniques; Electrochemical sensors and biosensors; Mosquito-borne diseases and control